An Evaluation of Age-Group Latent Mean Differences in Maladaptive Identity in Adolescence - Sharp, Carla; Vanwoerden, Salome; Schmeck, Klaus; Birkhölzer, Marc; Goth, Kirstin (Frontiers in Psychiatry, 2021)
Little is known about the differences between age groups in maladaptive personality function as denoted in Criterion A of the Alternative Model for Personality Disorder (AMPD) in the DSM-5. The current study aimed to address this gap by evaluating latent mean age group differences in maladaptive identity, which is one aspect of DSM-5 Criterion A (Level of Personality Functioning; LPF) that has been identified as an important feature of maladaptive personality function. We were also interested whether mean differences would track with mean differences in borderline personality disorder (BPD) features given prior data suggesting that general personality function overlap with the construct of BPD. A community sample of N = 2,381 adolescents, representing a mix of different socio-economic and educational backgrounds, ages 12-18 (M = 14.92, SD = 1.94; 46% male) completed a measure of maladaptive identity. A subset (n = 1,165) completed a measure of borderline personality features. Latent variable modeling was used to evaluate latent mean differences across seven age bands. Results suggested a normative increase in maladaptive identity after age 12, which remained consistent until age 17 when it dropped back to levels observed in 12-year-olds. Maladaptive identity was significantly associated with mean-level increases in borderline personality features, with these constructs becoming more closely associated with increasing age.